LEXICAL LAYER MASTERED IN THE UZBEK DIALECTS OF QARLUQ TYPE - Yakubov Sadigjon Latif ugli (International Journal of Literature and Language Studies, 2026)
This article analyzes the formation, composition and linguistic features of the acquired lexical layer in the old Uzbek dialects. The study covered the level of use, semantic features and territorial distribution of words borrowed from Arabic, Persian-Tajik, Russian and other languages found in the lexicon of qarluq dialects. The role of absorption units in sheva's dictionary structure, their phonetic and semantic adaptation processes, and their interaction with local lexical units have also been considered. As a result of the analysis, it is based on the fact that the acquired layer is one of the important sources in the enrichment of the lexicon of the old-type Uzbek dialects, the assimilation of which manifests itself as an important linguistic phenomenon reflecting the historical progress of the dialects and language ties.